Human factors specification for a machine tool scale reader - Easterby, R. S. (College of Aeronautics, 1964)
The length measuring devices on many machine tools must usually cover a large range while maintaining high accuracy for small incremental movements. Many machines use the operator as part of the measuring system, where he must assign numerals and carry out visual interpolation. This report attempts to define the preferrred characteristics of such indication systems in so far as they are influenced by the capabilities and limitations of the human operator. While no radical innovations are proposed, the principles underlying the design of scale readers have been examined as objectively as possible and recommendations substantiated by reference to relevant experiments.